Whose Opinion Is It? Public Debates and Repertoires of Action in Greece During the First Covid-19 Lockdown Period - Chatzopoulou, Sevasti; Exadaktylos, Theofanis (Javnost-The Public, 2021)
To what extent do public health crises create unity or polarise the public sphere? We investigate the development and dynamics of the public debate in Greece in light of Covid-19 to detect polarisation within the public sphere. We cover the first wave of the pandemic (March-May 2020), assessing reactions to government measures. In times of crises, the public looks for shortcuts in the media to assess the overabundance of information and digest the complexity of a crisis. Hence, people look at opinion leaders for guidance or to reinforce their own views. To assess the formation of the public debate and public responses we look at the cues the public receives via the media. Through a content analysis of editorial pieces in Greek newspapers we code references to government responses, the public response or the responsibility of fellow citizens, and the role of experts in providing professional advice to the government and guidance to society. The differential of positive and negative references reflects and determines a polarised debate that triggers public mobilisation and engagement with specific repertoires of action. The findings assist in understanding the adherence to government guidance by the public and the passive reception or contestation of measures.